PENGARUH FAKTOR PENDIDIKAN DAN PEKERJAAN TERHADAP TINGKAT PEMAHAMAN DAN PENERAPAN HIGIENE DAN SANITASI PENGOLAHAN DAGING AYAM DI TINGKAT RUMAH TANGGA DI KOTA KUPANG - Margie Mila Meha; Diana A. Wuri; Annytha Ina Rohi Detha (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
The aims of this study were to know the influence of education level and type of work against the level of understanding and application hygiene and sanitation processing of chicken meat by housewives in Kupang City. Determination the quantity of samples is done with software Win Episcope® 2.0 with level of confidence 95%, expected prevalence 50%, and accepted error 5%, then total of 220 respondents involved in this study. Samples carried out by simple random sampling to determine the area (RW) that elected per sub district. Assessment the level of understanding and application of sanitary hygiene is performed by summing the score answers of each item contained in the questionnaire. The data were analyzed descriptively and correlation between the characteristics of the respondents determined by Spearman test. The results showed that most housewife with low education level and not working have a good level of understanding (n=81; 73.6%) and application of sanitation hygiene categorized enough (n=65; 59.1%), housewives with low levels of education and work have a good level of understanding (n=77; 70%) and the application of sanitation hygiene categorized enough (n=65; 59.1%). Spearman correlations test show that there were noticeable at low-educated housewife and not working (p<0.05), and low-educated housewife and working (p<0.05).